Muppets most wanted - Gervais, Ricky; Bonneville, Hugh.; Bennett, Tony.; Fey, Tina.; Burrell, Ty.; Goelz, Dave.; Whitmire, Steve; Jacobson, Eric. ([United States] : Walt Disney Studios Home Entertainment, 2014)
The entire Muppets gang goes on a global tour, selling out grand theaters in some of Europe's most exciting destinations, including Berlin, Madrid, Dublin and London. But mayhem follows the Muppets overseas, as they find themselves unwittingly entangled in an international crime caper headed by Constantine-the World's Number One Criminal and a dead ringer for Kermit the Frog-and his dastardly sidekick Dominic, aka Number Two.
Director, James Bobin.
Hugh Bonneville, Eric Jacobson, Tina Fey, Ty Burrell, Dave Goelz, Tony Bennett, Ricky Gervais, Steve Whitmire.
MPAA rating: PG.
DVD.
English, Spanish audio; English, French, Spanish subtitles.
English subtitles for the deaf and hard of hearing.